2005
DOI: 10.1093/brain/awh700
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection against ischaemic brain injury by a GluR6-9c peptide containing the TAT protein transduction sequence

Abstract: It is well documented that N-methyl-D-aspartate and alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors play a pivotal role in ischaemic brain injury. Recent studies have shown that kainate (KA) receptors are involved in neuronal cell death induced by seizure, which is mediated by the GluR6*PSD-95*MLK3 signalling module and subsequent c-Jun N-terminal kinase (JNK) activation. Here we investigate whether GluR6 mediated JNK activation is correlated with ischaemic brain injury. Our results show that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 39 publications
3
106
0
Order By: Relevance
“…S7100) was purchased from Chemicon International, Inc. KA was from BIOMOL. Tat-GluR6-9c (Arg-Leu-Pro-Gly-Lys-Glu-Thr-MetAla, GluR6-9c), a 20-amino acid fusion peptide with Tat protein (Tyr-Gly-Arg-Lys-Lys-Arg-Arg-Gln-Arg-Arg-Arg), and Tat-GluR6AA (Tat-Arg-Leu-Pro-Gly-Lys-Ala-Ala-Asp-Asp) were constructed in our laboratory (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7100) was purchased from Chemicon International, Inc. KA was from BIOMOL. Tat-GluR6-9c (Arg-Leu-Pro-Gly-Lys-Glu-Thr-MetAla, GluR6-9c), a 20-amino acid fusion peptide with Tat protein (Tyr-Gly-Arg-Lys-Lys-Arg-Arg-Gln-Arg-Arg-Arg), and Tat-GluR6AA (Tat-Arg-Leu-Pro-Gly-Lys-Ala-Ala-Asp-Asp) were constructed in our laboratory (19).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (19), we demonstrated that Tat-GluR6-9c, a GluR6 C terminus-containing peptide conjugated to the cell membrane transduction sequence of the human immunodeficiency virus Tat protein, can be delivered into hippocampal neurons in vitro and in vivo. In the present study, we demonstrate that Tat-GluR6-9c can perturb the interaction of GluR6 with PSD95 and suppress the assembly of the * This work was supported by Grant 30330190 from the Key Project of the National Natural Science Foundation of China.…”
mentioning
confidence: 97%
“…Subsequently, several other studies have also reported effective biodistribution of therapeutically important proteins in vivo by using PTD [52,[69][70][71][72][73][74][75]. In a previous study, however, no PTD mediated transduction in brain was observed, [46] possibly because beta-gal was chemically conjugated to PTD instead of recombinant fusion protein.…”
Section: Potential Of Ptd-fusion Protein Transduction In Vivomentioning
confidence: 99%
“…Excessive stimulation of GluK2-containing kainate receptors mediates the activation of proapoptotic JNK3 signaling, which is responsible for postischemic delayed neuronal loss (24). It has been found that sustained agonist treatment induces the endocytosis of GluK2-containing kainate receptors (31).…”
Section: Gluk2 Phosphorylation At Y590 Facilitates Kainate Receptormentioning
confidence: 99%
“…Glutamate-induced intracellular Ca 2+ ([Ca 2+ ] i ) overload is a major mechanism underlying excitotoxicity and ischemic cell death. Furthermore, excessive activation of GluK2-containing kainate receptors triggers the proapoptotic JNK signal cascade, which contributes to ischemic brain damage (23,24). These findings suggest that GluK2-containing kainate receptor-mediated responses are critical events in the induction of neuronal cell death after stroke.…”
mentioning
confidence: 98%